2012
DOI: 10.1210/en.2012-1464
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol and Progesterone Regulate Expression of β-Amyloid Clearance Factors in Primary Neuron Cultures and Female Rat Brain

Abstract: The accumulation of β-amyloid protein (Aβ) is a key risk factor in the development of Alzheimer's disease. The ovarian sex steroid hormones 17β-estradiol (E(2)) and progesterone (P(4)) have been shown to regulate Aβ accumulation, although the underlying mechanism(s) remain to be fully elucidated. In this study, we investigate the effects of E(2) and P(4) treatment on the expression levels of Aβ clearance factors including insulin-degrading enzyme, neprilysin, endothelin-converting enzyme 1 and 2, angiotensin-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 82 publications
2
52
2
2
Order By: Relevance
“…This was paralleled by increased expression of genes involved in Aβgeneration. In addition to its role in promoting insulin/IGF-1 function, estrogen further promotes Aβdegradation and clearance by upregulating insulin-degrading enzyme (IDE) and neprilysin gene and protein expression (Jayaraman et al, 2012; Zhao et al, 2011b). …”
Section: Estrogen and Brain Bioenergeticsmentioning
confidence: 99%
“…This was paralleled by increased expression of genes involved in Aβgeneration. In addition to its role in promoting insulin/IGF-1 function, estrogen further promotes Aβdegradation and clearance by upregulating insulin-degrading enzyme (IDE) and neprilysin gene and protein expression (Jayaraman et al, 2012; Zhao et al, 2011b). …”
Section: Estrogen and Brain Bioenergeticsmentioning
confidence: 99%
“…The level of C83 is much higher than that of C99, which is expected since non-amyloidogenic cleavage by α-secretase is the predominant pathway for APP processing (Postina, 2008). We tested the effect of FAC on Aβ levels using a validated colorimetric ELISA (Dasari et al, 2010; Jayaraman et al, 2012; Thakker et al, 2009), which showed an increase in Aβ42, with no detectable change in Aβ40 (Fig. 3D).…”
Section: Resultsmentioning
confidence: 99%
“…The direct progesterone protecting actions against AD development and/or progression include regulation of β-amyloid metabolism by reducing Aβ production and decreasing the pool of soluble Aβ by enhancement of the non-amyloidogenic α-secretase pathway, decreasing Aβ accumulation through modulation of γ-secretases activities and increasing Aβ clearance by enhancing insulin-degrading enzyme expression and downregulation of β-secretase gene expression [85,86]. At the same time, progesterone reduces tau hyperphosphorylation and the serum level of endogenous progesterone is inversely correlated with tau accumulation, and at the same time, progesterone administration in transgenic AD mice improved cognitive performance in object recognition and T-maze task [87].…”
Section: Progesterone and Alzheimer's Diseasementioning
confidence: 99%